The Effectiveness of Ultrasound Surveillance for Hepatocellular Carcinoma in a Canadian Centre and Determinants of Its Success - Korosh Khalili; Ravi Menezes; Tae Kyoung Kim; Leyla Kochak Yazdi; Hyun-Jung Jang; Suraj Sharma; Jordan Feld; Morris Sherman (Canadian Journal of Gastroenterology and Hepatology)
BACKGROUND: The effectiveness of surveillance for hepatocellular carcinoma (HCC) using ultrasound (US) in North America has been questioned due to the predominance of patients of Caucasian ethnicity and larger body habitus.